Design of Frequency Reconfigurable Antenna Array Element for L and C Band Applications - et al., B.Neeththi Aadithiya (International Journal of Control and Automation, 2019)
A recurrence reconfigurable space ring receiving wire exchanging among L and C groups is exhibited. Opening of a L-band space ring reception apparatus can be reconfigured to a 2x2 C-band opening ring receiving wire exhibit by changing the conditions of 16 PIN diode switches. This receiving wire works at 1.76/5.71 GHz in L/C band working states separately. The deliberate acknowledged addition and radiation effectiveness are 0.1/4.2dB. Estimated results demonstrate that the PIN diode switches make them load impacts on the receiving wire. Parametric investigation of each circuit component is likewise reenacted and given in this paper. programming utilized is HFSS for reproduction. The proposed receiving wire is intended to emanate and transmit measure up to measures of intensity. The arrival loss of the proposed reception apparatus is higher than that ideal for one-port receiving wire application at the ideal double band frequencies.